2014
DOI: 10.1590/0103-8478cr20131099
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvantes em pulverizações de fungicidas na cultura do trigo

Abstract: RESUMO As doenças foliares e da espiga podem reduzir acentuadamente a produtividade da cultura do trigo. Apesar de prevalecer o controle químico no manejo das doenças, os estudos com adjuvantes para melhoria do desempenho de fungicidas ainda são incipientes. O objetivo deste trabalho foi avaliar o efeito

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…The variables that differed significantly were grains per pod, pods per plant and productivity. Thus, we confirm the importance of chemical control, within the integrated management of diseases (Garcia et al, 2002;Vieira et al, 2012;Cunha et al, 2014;Souza et al, 2014;Garcia et al, 2016;Tackenberg, et al, 2016).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The variables that differed significantly were grains per pod, pods per plant and productivity. Thus, we confirm the importance of chemical control, within the integrated management of diseases (Garcia et al, 2002;Vieira et al, 2012;Cunha et al, 2014;Souza et al, 2014;Garcia et al, 2016;Tackenberg, et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…However, the occurrence and incidence of diseases stands out as one of the main limiting factors for crop productivity. In the integrated pathogens management, the use of appropriate techniques to place the pesticides in the targeted pathogen is crucial for an effective disease control (Garcia et al, 2002;Souza et al, 2014;Garcia et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente, desenvolveu-se adjuvantes naturais baseados em óleos essenciais extraídos da casca de laranjas (Citrus spp. L.), no entanto, há carência de informações sobre sua eficiência (Souza et al, 2014;Coradini et al, 2016;Zampiroli et al, 2019). Diante do exposto o presente trabalho teve como objetivo comparar o produto comercial Valio a base de óleo de laranja com óleo mineral e adjuvante na deposição de gotas de pulverização de produtos químicos nos alvos desejados na aplicação terrestre.…”
Section: Introductionunclassified
“…Spray adjuvant is used in pesticide applications to alter the physicochemical properties of spray solutions and to increase their effectiveness (Chuah, Tan, & Ismail, 2013). Several studies on the addition of adjuvants to spray solutions have confirmed positive effects of adjuvants on the control of weeds and fungi (Gauvrit, Müller, Milius, & Trouvé, 2007;Souza et al, 2014). These positive effects can be attributed to changes in the physicochemical properties of the spray solution, such as conductivity, viscosity, and surface tension (Sasaki et al, 2015).…”
mentioning
confidence: 98%